2020
DOI: 10.1111/ene.14175
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of oral anticoagulant interruption among stroke patients with atrial fibrillation and subsequent stroke

Abstract: Background and purpose: We analyzed the incidence and causes of oral anticoagulant (OAC) cessation and subsequent stroke after OAC withdrawal in a cohort of Korean stroke patients with atrial fibrillation. Methods: The Korean Atrial Fibrillation Evaluation Registry in Ischemic Stroke patients (K-ATTENTION) is a multicenter cohort study, merging stroke registries from 11 tertiary centers in Korea. The number of OAC interruption episodes and the reasons were reviewed from hospital records. Stroke after OAC withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the univariate and multivariate analyses, AF status was significantly associated with recurrence. A previous study showed that medication for secondary prevention was insufficiently administered to eligible patients (26). Another study showed that anticoagulants could reduce the risks of ischemic stroke events in patients with ischemic stroke and AF (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the univariate and multivariate analyses, AF status was significantly associated with recurrence. A previous study showed that medication for secondary prevention was insufficiently administered to eligible patients (26). Another study showed that anticoagulants could reduce the risks of ischemic stroke events in patients with ischemic stroke and AF (27).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of European Journal of Neurology [1], Kim et al. bring to us a relevant study on the incidence of oral anticoagulant (OAC) interruption in patients with atrial fibrillation and subsequent stroke.…”
mentioning
confidence: 99%